The evaluation of hepatoprotective effects of flavonoids from Scorzonera austriaca Wild against CCl4-induced acute liver injury in vitro and in vivo. (4th May 2022) - Wei, Enwei; Zhang, Sixi; Zhai, Jinghui; Wu, Sitong; Wang, Guangshu
Abstract: Scorzonera austriaca Wild is a traditional herbal medicine; however, little is known with regard to the effect of flavonoids from S. austriaca (FSA) on liver injury induced by Carbon tetrachloride (CCl4 ), especially the mechanism remains unknown. Therefore, our paper was designed to investigate the hepatoprotective effect of FSA against CCl4 -induced acute liver injury in vitro and in vivo, with focus on its potential mechanism. The purity of FSA prepared by using polyporous resin column chromatography could reach 94.5%, and seven flavonoid compounds in FSA were identified by using LC-ESI-MS analysis. In vivo results showed that FSA markedly decreased the levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and malonaldehyde (MDA) and increased the contents of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). Furthermore, in vivo and in vitro results confirmed that FSA could inhibit inflammatory response, as evidenced by decreasing the levels of tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) through inactivating toll-like receptor-4/nuclear factor-κB (TLR4/NF-κB) signaling pathway. FSA activated autophagy by increasing the ratio of LC3B-II/I and decreasing the protein level of p62 so as to exert its hepatoprotective effect. In general, these evidences suggested that FSA is likely to serve as a potential material for the drugs against chemical hepatic injury.